2019
DOI: 10.32474/ado.2019.02.000128
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Malnutrition in Older Hospitalised Patients in an Internal Medicine Department of a Greek Public Hospital

Abstract: Background: Malnutrition is a major public health concern that frequently tends to be unrecognized and untreated. About 1/3 of all patients in the hospital are undernourished globally. Malnutrition is significantly more common in older adults, and consequently they are in danger of suffering from malnutrition prior to their admission. Aim:The objectives of the present study were to estimate the prevalence and severity of malnutrition, along with recent weight loss, in older adults admitted to a department of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…Due to their favorable effects, it is recommended that physicians prescribe ONSs to old, malnourished patients [17]. In a study conducted on the elderly in the internal medicine service in Greece, it was observed that ONSs were initiated in 8 out of 25 malnutrition patients, and the rate was higher than in our study [44]. In our study, only 7 of 31 malnutrition patients were administered ONSs, which suggests that dietitians were not consulted and that doctors and nurses need more training about ONSs.…”
Section: Discussioncontrasting
confidence: 66%
“…Due to their favorable effects, it is recommended that physicians prescribe ONSs to old, malnourished patients [17]. In a study conducted on the elderly in the internal medicine service in Greece, it was observed that ONSs were initiated in 8 out of 25 malnutrition patients, and the rate was higher than in our study [44]. In our study, only 7 of 31 malnutrition patients were administered ONSs, which suggests that dietitians were not consulted and that doctors and nurses need more training about ONSs.…”
Section: Discussioncontrasting
confidence: 66%